Diagnostic Value of Integrated Serum Protein Carbonyl, 8-Hydroxy-2'-Deoxyguanosine, and PGC-1α Profiling for Myocardial Energy Metabolism Disorder in Ischemic Cardiomyopathy - Wang, Qingli; Liu, Bei (Journal of Medical Biochemistry, 2026)
Background: Patients with ischemic cardiomyopathy (ICM) often have abnormalities in myocardial energy metabolism, whereas conventional cardiac function indices may not capture metabolic injury in a timely manner. This study aimed to evaluate the diagnostic value of combined serum protein carbonyl (PC), 8-hydroxy-2'-deoxyguanosine (8-OHdG), and peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) detection for myocardial energy metabolism disorder in patients with ICM.Methods: A total of 167 patients with ICM hospitalized between June 2024 and October 2025 were retrospectively enrolled. According to myocardial energy metabolism status, they were divided into an energy metabolism disorder group (n=78) and a non-disorder group (n=89). Serum PC, 8-OHdG, and PGC-1α levels were measured. Clinical data, cardiac function indices, and serum biomarker levels were compared between the two groups. A combined diagnostic model was then constructed using logistic regression, and receiver operating characteristic (ROC) curves were used to evaluate the diagnostic performance of single indicators and combined detection.Results: Compared with the non-disorder group, the energy metabolism disorder group showed increased PC and 8-OHdG levels and decreased PGC-1α levels, with statistically significant differences (P
Keywords: Ischemic cardiomyopathy; myocardial energy metabolism disorder; protein carbonyl; 8-hydroxy-2'-deoxyguanosine; PGC-1α; diagnostic model